Liposomes containing sorbitan monolaurate incorporated in hydroxyethylcellulose hydrogels for topical delivery of 5-fluorouracil: rheological characterization, skin penetration and cytotoxicity study - Carvalho, Genuína Stephanie Guimarães; Reis, Alice Vitoria Frota; Crisóstomo, Luiziana Cavalcante Costa Fernandes; Dos Santos, Aline Martins [UNESP]; Araújo, Tamara Gonçalves; Chorilli, Marlus [UNESP]; Petrilli, Raquel; Eloy, Josimar O (Elsevier, 2025)
In this work, liposomes composed of soy phosphatidylcholine (SPC) and cholesterol (CHOL), in addition to sorbitan monolaurate (span 20), a skin penetration enhancer, were incorporated into hydroxyethylcellulose (HEC) hydrogels to optimize the topical administration of 5-fluorouracil (5-FU) employed in treatment of skin cancer. The formulations were stable (pH, density, viscosity) in the period of 30 days. Furthermore, the pseudoplastic behavior with thixotropy of the developed hydrogels, in the presence or absence of liposomes, was confirmed, proving that liposome incorporation does not compromise their rheological characteristics, maintaining desirable aspects for topical application. Texture and bioadhesion studies also demonstrated the ability of hydrogels associated with liposomes to present good spreadability in parallel with increased contact time of the drug on the skin. Although it was not possible to quantify the active ingredient from the hydrogels, the in vitro release test allowed us to observe a prolonged release of 5-FU by the nanocarriers, which, associated with the polymeric matrix, suggests a system capable of protecting the drug from the physiological environment, while providing effective delivery. Liposomes containing span 20, incorporated into the HEC hydrogel, were capable of delivering 1194,8 ng/cm2 of 5-FU into viable epidermis + dermis, observed in the in vitro skin penetration study, unlike samples containing liposomes without span, in which it was not possible to quantify the drug in the skin layers. Therefore, not only we were able to show the potential of span 20 to promote drug skin penetration, but we also proved that with the incorporation of liposomal dispersions in HEC hydrogels, fundamental for enabling their topical application, this property is maintained. Finally, in vitro cytotoxicity evaluated in the A431 cell line provided IC50 values of 1.953 μM, corroborating that hydrogels containing span 20 liposomes containing 5-FU are indeed a promising strategy for potential treatment of skin cancer.